The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.14453/aabfj.v8i4.7
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Manipulation on the Hong Kong Stock Exchange

Abstract: This study is the first to empirically examine stock market manipulation on the Hong Kong Stock Exchange. The dataset contains 40 cases of market manipulation from 1996 to 2009 that were successfully prosecuted by the Hong Kong Securities & Futures Commission. Manipulation is found to negatively impact market efficiency measures such as the bid-ask spread and volatility. Markets appear incapable of efficiently responding to the presence of manipulators and are characterised by information asymmetry. Manipulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…In general, excess return is defined as any risk adjusted return that is above the return suggested by a pricing model, i.e., CAPM. A study of 40 incidences of stock market manipulation in Hong Kong Stock Exchange revealed the relationship between market manipulation and artificially generated excess return (Gerace et al, 2014). Excess return certainly can be caused by other non-manipulative reasons and is not always an indication of manipulation, however, is a major candidate for being one of the observable indicators in our model.…”
Section: Indicators and Casual Variables Of Manipulationmentioning
confidence: 97%
“…In general, excess return is defined as any risk adjusted return that is above the return suggested by a pricing model, i.e., CAPM. A study of 40 incidences of stock market manipulation in Hong Kong Stock Exchange revealed the relationship between market manipulation and artificially generated excess return (Gerace et al, 2014). Excess return certainly can be caused by other non-manipulative reasons and is not always an indication of manipulation, however, is a major candidate for being one of the observable indicators in our model.…”
Section: Indicators and Casual Variables Of Manipulationmentioning
confidence: 97%
“…Gerace, Chew, Whittaker and Mazzola (2014) examine the impact of stock market manipulation on the HKSE. The authors recommend deterrence of such manipulation through stronger enforcement.…”
Section: Editorial: Aabfj Volume 8 Issue 4 Special Issue In Financiamentioning
confidence: 99%
“…(CFA Institute, 2015). Therefore, market manipulation is an important issue to detect and prevent across all of the financial markets including the US and the European and the emerging markets (Aggarwal & Wu, 2003;Cumming et al, 2015;Gerace et al, 2014;Imisiker & Tas, 2013;Khwaja & Mian, 2005;Lee et al, 2013;Mei et al, 2004;Öğüt et al, 2009;Punniyamoorthy & Joy Thoppan, 2012).…”
Section: Introductionmentioning
confidence: 99%